Spectroscopic analysis of chlamydial major outer membrane protein in support of structure elucidation. (25th October 2018) - Hepler, Robert W.; Nahas, Debbie D.; Lucas, Bob; Kaufhold, Robin; Flynn, Jessica A; Galli, Jennifer D.; Swoyer, Ryan; Wagner, James M.; Espeseth, Amy S.; Joyce, Joseph G.; Cook, James C.; Durr, Eberhard
Abstract: Chlamydial major outer membrane protein (MOMP) is the major protein constituent of the bacterial pathogen Chlamydia trachomatis. Chlamydia trachomatis Serovars D–K are the leading cause of genital tract infections which can lead to infertility or ectopic pregnancies. A vaccine against Chlamydia is highly desirable but currently not available. MOMP accounts for ~ 60% of the chlamydial protein mass and is considered to be one of the lead vaccine candidates against C. trachomatis . We report on the spectroscopic analysis of C. trachomatis native MOMP Serovars D, E, F, and J as well as C. muridarum MOMP by size exclusion chromatography multi angle light scattering (SEC MALS), circular dichroism (CD) and attenuated total reflectance Fourier transform infrared spectroscopy (ATR‐FTIR). MOMP was purified from the native bacterium grown in either adherent HeLa cells or in different suspension cell lines. Our results confirm that MOMP forms homo‐trimers in detergent micelles. The secondary structure composition of C. trachomatis MOMP was conserved across serovars, but different from composition of C. muridarum MOMP with a 13% (CD) to 18% (ATR‐FTIR) reduction in β‐sheet conformation for C. trachomatis MOMP. When Serovar E MOMP was isolated from suspension cell lines the α‐helix content increased by 7% (CD) to 13% (ATIR‐FTIR). Maintenance of a native‐like tertiary and quaternary structure in subunit vaccines is important for the generation of protective antibodies. This biophysical characterization of MOMP presented here serves, in the absence of functional assays, as a method for monitoring the structural integrity of MOMP.